Efeito de borda na estrutura, diversidade e fenologia de floresta tropical estacional submontana - Santos, Ana Paula Lima do Couto (2014)
(Effect of edge in structure, diversity and phenology in seasonal tropical forest submontane) Forest fragmentation causes physical and biological changes with habitat loss and insularization of populations, and the edge effect the most obvious consequence of this process. Thus, this study aimed to investigate the effect of linear edge in a fragment of submontane seasonal forest in the Chapada Diamantina, Bahia, Brazil (12º28'31 "S and 41º23'14''W) in order to analyze the structure and composition vegetation, reproductive phenology and the vegetative phenology, classifying the forest as their leaf pattern, and the functional diversity. Were marked 30 plots (10 x 10 m) random and 15 at the forest edge (0 - 100m) and 15 inside (> 150m) in the power line high voltage. For structural studies were marked all individuals with diameter at breast height ≥5 cm. The species were classified according to successional category and phytosociological parameters were calculated and diversity indices. The Shannon - Wiener index was compared by t test Hutcheson and the other parameters by ANOVA. From this study the species with the highest importance value and abundance for the other investigations were chosen. In the reproductive phenological study monthly observations were made over 26 months in 481 individuals (282 on the edge (61 species) and 199 inside (50 species) of forest), recording the presence and absence of flowering (and flower button) and fruiting (immature and mature fruit) for all life forms. It is estimated timing, frequency and duration of phenological events and the species were classified as the pollination and dispersal syndromes. Data were analyzed with G test, linear regression and circular statistics. In the study of functional diversity created a matrix of functional traits to the edge and interior including phenological, structural and reproductive aspects. Measurements of leaf traits (thickness, dry dough sheet per unit area, juiciness, density, leaf area ratio and leaf mass fraction), density and wood water saturation were carried out in the dry and wet seasons (September / 2012 and January / 2013) in 20 species. Regressions were made between phenophases and environmental variables (precipitation, temperature, relative humidity, photoperiod and heat stroke), circular statistics and comparisons of leaf traits and wood density between the dry and rainy season through the G test and ANOVA. The species ordination in relation to leaf and wood attributes was evaluated by Principal Component Analysis (PCA). The functional groups were defined by cluster analysis with distance Gower and calculated indexes Functional richness (FRic), Functional divergence (FDiv), Functional evenness (FEve), Functional dispersion (FDis). ANOVA and linear regression were used to evaluate the rates between areas. In vegetative phenological study followed up the budding and leaf fall 350 individual trees in the community (39 species). Increase the impact of straight edge on the floristic composition was checked, the diversity and abundance of species, while less interference was observed in the tree community structure, as phytosociological parameters and ratios between the guilds did not differ significantly between edge and interior fragment. The phenological analysis revealed that flowering and fruiting at the edge and interior were continued for long, low-intensity periods, asynchronous and assazonal being for most phenophases, with a significant difference in the individual to button number. Seasonality in flowering and fruiting were observed for bush and grass land in both areas and epiphytes to the edge. Similar proportions in the number of species for pollination and dispersal syndromes were found on the edge and inside, with a predominance of melittophilous and animal dispersed species. The vegetation was evergreen, with budding and continuous leaf fall, low intensity and low sync. The leaf bud was related to rainfall and sunshine and fall with precipitation and humidity. Significant variation between the dry and wet seasons were observed in the proportion of saturated water in the wood, leaf area ratio and leaf succulence. ACP showed greater variance for wood density (88.7%) and stored water (11.3%), gathering most species with standard perenifólios phenological and episodic perenifólios, other attributes showed no relevance to the phenological patterns. The main functional groups formed on the edge and inside were similar, defined based on the way of life, stratum and pollination and dispersal. Of co-occurring species (40 species), 22.5% belong to different functional groups due to different growth patterns. The functional diversity indices showed higher mean values for the edge, except that Fric was higher in the forest. These were not affected by the distance to the edge. Changes were observed inside in relation to species richness and Shannon - Wiener only for Fric. The implementation of linear infrastructure brings similar impacts to those coming from other types of edges in community structure. In other aspects analyzed the changes were subtle for the tree community, but the same was not true for shrubs, herbs and vines. The vegetation can be classified as seasonal submontane rainforest always green, with small annual variation in the physiognomy of the vegetation, and the perenifólios and perenifólios types episodic predominant both in number of species and in their abundance. The leaf traits showed no relevance to phenology, not being good descriptors for the seasonal evergreen forest. There is no significant difference in functional diversity, but the highest rate obtained inside for functional wealth reflects the biological loss caused by the installation on the edge of the linear edge. Appearance evidenced by the greater abundance of Eschweilera tetrapetala Mori inside, an endemic species of submontane forests of the region. This study contributes to future conservation work to note the interference the linear edge on the forest ecosystem, as well as to the classification of the Brazilian forests, to verify the occurrence of seasonal evergreen forests in the Caatinga.